Doing Best for Children: - Ruth Freeman; Richard Ekins; Michele Oliver (Grounded Theory Review: An International Journal, 2005)
Changes in children’s lifestyle from structured family meals to unstructured between meal sugar snacking has been recognised as a risk factor in childhood obesity. Parental insights into children’s between meal snacking and their experiences of regulation are important if an understanding of sugar snacking is to be gained in the field of childhood obesity. The aim of this study was to use grounded theory techniques to analyze the qualitative data obtained from participants and to generate an emerging theory of snack regulation. A series of focus groups with parents and their children were conducted. Data were analysed using grounded theory techniques. The core category that emerged from the data was ‘doing best’. Parents used the behavioural strategy of policing as a consequence of doing best. Parents had to balance time availability, disposable income, energy levels, parental working patterns and family life with the child’s food wishes and social needs. Balancing such contextual constraints influenced the style of policing.